Effects of HIPS on the Sound Absorption and Impedance Ratio of SEBS/HIPS/CaCO3 Polymer Composites - TAŞDEMİR, MÜNİR; ERSOY, SEZGİN (TAYLOR & FRANCIS INC, 2012)
A sound absorption material composed of styrene ethylene butadiene styrene, high impact polystyrene and CaCO3 has been developed. Its sound absorbing characteristic was investigated in the impedance tube, according to transfer function method. Measurements show that HIPS ratios have effect on the absorption performance of the blend because of their microstructures and features. The structure and properties of the blend is characterized using a scanning electron microscopy (SEM). Furthermore, styrene ethylene butadiene styrene and high impact polystyrene polymer blend was subjected to examinations to obtain their hardness and Izod impact strength. When the sound absorption characteristics of the materials are examined, a unsteady behaviour is observed up to the level of 1600 Hz. It is determined that sound absorption characteristics of all materials increase after this point. A high and steady behaviour is observed, particularly after 4800 Hz.
Keywords: High impact polystyrene; Impedance ratio; Insulation; Polymer blends; Sound absorption; Styrene ethylene butadiene styrene; Thermoplastic elastomer